Eicosapentaenoic Acid as Adjuvant for Cachexia in Cancer’s Patients - Soeseno Hadi; Cynthia Kurniawan; Jansen Budiono (Faculty of Medicine Universitas Padjadjaran, 2015)
Cachexia is a frequent problem in cancer patients associated with mortality and morbidity since it causes death, reduced therapy effectiveness, as well as decreased quality of life. Cachexia emerges from interactions of several factors, namely metabolic effect of cancer cells, factors released by cancer cells, cytokines release from host cell in response to tumors, and side effects of therapies. Combination of these factors contributes to anorexia, decreased body fat and muscle, and weight loss. Unfortunately, there is no gold standard for treatment of cachexia. Several studies found that eicosapentaenoic acid (EPA) might improve cancer cachexia. It has potential blocking effects on several cachexia underlying factors. It may reverse weight loss, increase lean body mass, and improve the efficacy of therapy and the quality of life. The objective of this literature review is to describe and give basic understanding of EPA as adjuvant for cancer cachexia. Keywords: Cachexia, cancer, EPADOI: 10.15850/ijihs.v3n1.399